Capillary driven flow in wettability altered microchannel. Issue 10 (18th May 2017) - Sett, Ayantika; Bano, Uzma; DasGupta, Sunando; Sarkar, Debasish; Mitra, Arijit; Das, Siddhartha; Dasgupta, Swagata
Abstract : The capillary driven flow of water inside a microchannel with altered wettabilities is experimentally investigated and modeled theoretically. The surfaces of the PDMS made microchannel are exposed to oxygen plasma, rendering the surfaces increasingly hydrophilic, which provides the driving force for the flow. The plasma treated surfaces are characterized using topography and phase imaging of AFM scanning, as well as nano‐indentation, to correlate the distinct structural changes to the hydrodynamic profiles of the advancing meniscus. The experimental results are further analyzed using a newly proposed slip velocity model. The aim is to obtain a qualitative relationship between the surface properties and the flow parameters, namely the advancing meniscus velocity and pressure drop inside the channel. The insights are of fundamental importance in diverse fields, such as enhanced oil recovery, microfluidic devices, cell separation, and pathology. © 2017 American Institute of Chemical Engineers AIChE J, 63: 4616–4627, 2017